Influential factors for a secure perception of accounting management with blockchain technology - Emilio Abad-Segura; Alfonso Infante-Moro; Mariana-Daniela González-Zamar; Eloy López-Meneses (Journal of Open Innovation: Technology, Market and Complexity, 2024)
The scope of blockchain technology, initially associated with the Bitcoin cryptocurrency, is greater due to the multiple applications in various disciplines. Its use in accounting lies mainly in the fact that it reduces the risks and the possibility of fraud, in addition to eliminating human error. This work presents a theoretical model that contributes to the understanding of the process of adoption of ICT innovations by business organizations, from the technological, organizational and environmental contexts. The result of the work provides knowledge for the empirical generalization of the topic of study and offers the academic community a starting point for carrying out future studies that confirm the validity of the results, and the business community a valid alternative of the aspects to be considered taken into account in making decisions derived from secure accounting management with blockchain. Hence, the implementation of blockchain presents challenges, its potential to improve reliability and efficiency in accounting management makes this technology a valuable investment for companies and accounting professionals seeking more secure and transparent financial management.